Analysis of O2 Sensor Troubleshooting on Exhaust Gas Emissions and Fuel Consumption at Piksi Ganesha Indonesia Polytechnic - Devi Septiyani; Bahtiar Wilantara; Ismail Kholid; Sidik Purnomo (Politeknik Piksi Ganesha Indonesia, 2023)
This research aims to analyze O2 sensor troubleshooting on exhaust emissions and fuel consumption. The research method is comparative. Research steps by analyzing exhaust emissions and fuel consumption without an O2 sensor and with an O2 sensor at idle, 1000, 1500, and 2000 rpm. Research results: 1. comparison of exhaust emissions without O2 sensor and with O2 sensor, namely: idle rotation, CO = 7.41>3.33%, HC = 489 <497%, CO2 = 9.7 <12.5%, O2 = 13.44>0%, 1000 rpm, CO = 7.35>1.52%, HC = 686>538 ppm, CO2 = 9.7>11.8%, O2 = 10.91>2.20%, 1500 rpm, CO= 5.43>1.32%, HC= 666>472 ppm, CO2= 6.7>12.4%, O2= 13.25>4.95%, 2000 rpm, CO= 7.10>0.37%, HC= 499>272 ppm, CO2= 10.1<13.0%, O2= 11.24>9.03. 2. comparison of fuel consumption without o2 sensor and with o2 sensor, namely: idle rotation: 35=35ml, 1000 rpm: 15=15ml, 1500 rpm: 25>15ml, 2000 rpm: 15=15ml.